Tinjauan Yuridis Pertanggungjawaban Otoritas Jasa Keuangan dalam Penanggulangan Penipuan Investasi - Endi Suhadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to provide information about the responsibility of the Financial Services Authority (OJK) in dealing with investment fraud that often harms the community/consumers. Several cases of fraud cannot be properly identified by the Financial Services Authority, actions are taken after the investment institution is proven to have committed fraud. The research method used in this study is normative research strengthened by primary data regarding investment cases. The results of the study indicate that the responsibility of the Financial Services Authority is only in the form of administrative freezing after a fraud case occurs and cannot be requested for material losses because investment is in the private contract area so that it has not been carried out optimally. Legal protection carried out by the Financial Services Authority in the form of prevention, can be done with information services, education, and the existence of a kind of intelligence that actively seeks information on mass investment fraud information in the early stages (up liner).